Sex Steroids and Bone Health Status in Men - Kok-Yong Chin; Soelaiman Ima-Nirwana (International Journal of Endocrinology)
Male osteoporosis is a health problem which deserves more attention as nearly 30% of osteoporotic fractures happen in men aged 50 years and above. Although men do not experience an accelerated bone loss phase and testosterone deficiency is not a universal characteristic for aged men, osteoporosis due to age-related testosterone deficiency does have a negative impact on bone health status of men. Observations from epidemiological studies indicate that elderly men with higher testosterone can preserve their BMD better and thus are less prone to fracture. Observations on men with estrogen resistance or aromatase deficiency indicate that estrogen is equally important in the maintenance of bone health status. This had been validated in several epidemiological studies which found that the relationships between estrogen and bone health indices are significant and sometimes stronger than testosterone. Studies on the relationship between quantitative ultrasound and bone remodeling markers suggest that testosterone and estrogen may have differential effects on bone, but further evidence was needed. In conclusion, both testosterone and estrogen are important in the maintenance of bone health in men.